Perbandingan Pemidanaan bagi Psikopat dalam Hukum Pidana Indonesia dan Hukum Pidana Denmark - Asriel Bigtan; Sunardi Purwanda; Muhammad Darwis; Bakhtiar Tijjang; Kairuddin Kairuddin (JURNAL HUKUM PELITA, 2025)
Psychopaths as perpetrators of criminal acts, particularly in murder cases, pose complex problems in the field of criminal law due to their antisocial, manipulative, and unchangeable personality traits, which often render conventional punishment ineffective. This study aims to analyze the comparison of punishment for psychopathic perpetrators in murder cases between the Indonesian criminal justice system and the Danish criminal justice system. The research method used is socio-legal studies with a comparative approach, thereby enabling a description of the fundamental differences in the orientation of punishment in both countries. The results show that the Indonesian criminal justice system is still dominated by a punitive and general rehabilitation paradigm, without a specific design for prisoners with psychopathic disorders. This raises doubts about the effectiveness of punishment, particularly in relation to the prevention of recidivism, the limited number of experts, and the potential for abuse of the parole mechanism. In contrast, Danish criminal law recognizes the mechanism of forvaring, which emphasizes psychiatric rehabilitation and resocialization, reflecting a balance between protecting society and restoring individuals. This comparison shows that Indonesia places more emphasis on certainty and firmness in punishment, while Denmark prioritizes a long-term humanistic approach